Déficit de Alfa-1-antitripsina y su tratamiento - Cid Q., Catherina; Sbarbaro A., Daniella; Schilling, Sara; Silva S., Boris; Larraín, Diego; Mendoza I., Laura (Revista Hospital Clínico Universidad de Chile, 2017)
Alpha-1 antitrypsin deficiency (AATD) is a genetic disorder caused by a mutation in the codifying gene for the alpha-1 antitrypsin (AAT) protein, which has anti-elastase activity. While there is extensive genetic variability, the most common genotypes associated with AATD are PI*Z y PI*S. Most clinical manifestations are pulmonary (i.e. emphysema) and hepatic, though other pathologies, such as panniculitis and Wegener’s granulomatosis, can also present with this disorder. To date, there is no cure for AATD, and treatment options are focused on reducing the frequency of exacerbations and relieving symptoms; among these, augmentation therapy,which raises AAT levels through serum injections of the protein to correct the deficit, has been the most effective. Novel findings of this therapy are discussed, along with research efforts that explore new treatment options based on gene therapy or the use of protein chaperones, for instance. In Chile, no epidemiological studies on AATD have been conducted, so it is unknown exactly how many individuals are affected or if they receive adequate treatment.